Experiences and Perspectives of Transgender Individuals Accessing Gender-Affirming Care in Manitoba, Canada - Ezra Bridgwater; Gagan Gill; Jennifer Ducharme; Jennifer Hensel (SAGE Publishing, 2024)
As the number of trans people seeking gender-affirming care (GAC) continues to increase globally, it is increasingly important to understand the experiences of this patient population to improve healthcare delivery and ensure identified needs are being met. This qualitative descriptive study describes the experiences and perspectives of trans people (age 18-34) accessing GAC in Manitoba, Canada based on data obtained from semi-structured focus groups and individual interviews ( N = 10). Three major themes were identified to capture key elements of seeking GAC: (1) the transition decision, (2) the transition process, and (3) barriers to receiving desired care. In each major theme, subthemes were described. In addition to providing insight into critical aspects of this journey, this study also highlights the importance of including a diverse variety of perspectives when considering the design of healthcare services for the trans community.